PERHITUNGAN HARGA POKOK PRODUK DENGAN METODE FULL COSTING DAN VARIABLE COSTING UNTUK MENENTUKAN HARGA POKOK PROSES TERHADAP PERBANDINGAN LABA - Ika Neni Kristanti (JIAK : Jurnal Ilmiah Akuntansi dan Keuangan, 2015)
This study aims to determine the calculation of the cost of the process of knowing the comparison of profits in the calculation of the cost of the process between the full costing method and variable costing on SMEs "Batik Cap Pawitah". It can be seen that the results of the calculation of the cost of production using the full costing method experience a higher increase compared to using the variable costing method. Because in the calculation of full costing non-production costs are included and calculated. The full costing method is widely used for both internal and external reports. Some companies use a full costing approach because the approach focuses on the full costing of the production unit. While the variable costing method is useful in determining the cost of products and presenting cost information to meet management needs in planning and short-term decision making. Based on the profit / loss calculation, it is known that the calculation of profit / loss by using the full costing method produces greater profit than using the variable costing method.